2018
DOI: 10.1088/1475-7516/2018/05/048
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic structures and gravitational waves in ghost-free scalar-tensor theories of gravity

Abstract: We study cosmic structures in the quadratic Degenerate Higher Order Scalar Tensor (qDHOST) model, which has been proposed as the most general scalar-tensor theory (up to quadratic dependence on the covariant derivatives of the scalar field), which is not plagued by the presence of ghost instabilities. We then study a static, spherically symmetric object embedded in de Sitter space-time for the qDHOST model. This model exhibits breaking of the Vainshtein mechanism inside the cosmic structure and Schwarzschild-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…These references showed that for the subclass of these theories extending Horndeski, the two gravitational potentials differ inside matter and depend on the density profile, signalling the breaking of the Vainshtein screening. (See for instance also [27][28][29][30][31][32][33] for other studies on the surviving theories and [34,35] for reviews. )…”
Section: Introductionmentioning
confidence: 99%
“…These references showed that for the subclass of these theories extending Horndeski, the two gravitational potentials differ inside matter and depend on the density profile, signalling the breaking of the Vainshtein screening. (See for instance also [27][28][29][30][31][32][33] for other studies on the surviving theories and [34,35] for reviews. )…”
Section: Introductionmentioning
confidence: 99%
“…Although of course this does not encompass the most general set of scalar-tensor models, it should be clear that the general lessons we will draw should apply very generically. The case of quadratic DHOST theory is also worth focusing on given its interest in the astrophysical and cosmological literature (see e.g., [35][36][37][38][39][40][41][42][43]). Our analysis also opens the way to a classification based on matter coupling consistencies (in the above terminology) of the different scalar-tensor theories among themselves as well as compared with pure general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…The situation changes abruptly by the recent GW observations. The constraint on the propagation speed of GWs severely restricts theories of modified gravity for the late-time accelerated expansion [25][26][27][28][29][30] and those with the screening mechanism [31][32][33][34]. Moreover, the worldwide network of GW interferometer will include KA-GRA [35], and further improve these tests of gravity both on strong-field regime and cosmological scales.…”
Section: Introductionmentioning
confidence: 99%